Paravalvular Regurgitation: Clinical Outcomes in Surgical and Percutaneous Treatments - Pinheiro,Carlos Passos (2016)
Abstract Background: Paravalvular regurgitation (paravalvular leak) is a serious and rare complication associated with valve replacement surgery. Studies have shown a 3% to 6% incidence of paravalvular regurgitation with hemodynamic repercussion. Few studies have compared surgical and percutaneous approaches for repair. Objectives: To compare the surgical and percutaneous approaches for paravalvular regurgitation repair regarding clinical outcomes during hospitalization and one year after the procedure. Methods: This is a retrospective, descriptive and observational study that included 35 patients with paravalvular leak, requiring repair, and followed up at the Dante Pazzanese Institute of Cardiology between January 2011 and December 2013. Patients were divided into groups according to the established treatment and followed up for 1 year after the procedure. Results: The group submitted to percutaneous treatment was considered to be at higher risk for complications because of the older age of patients, higher prevalence of diabetes, greater number of previous valve surgeries and lower mean creatinine clearance value. During hospitalization, both groups had a large number of complications (74.3% of cases), with no statistical difference in the analyzed outcomes. After 1 year, the percutaneous group had a greater number of re-interventions (8.7% vs 20%, p = 0.57) and a higher mortality rate (0% vs. 20%, p = 0.08). A high incidence of residual mitral leak was observed after the percutaneous procedure (8.7% vs. 50%, p = 0.08). Conclusion: Surgery is the treatment of choice for paravalvular regurgitation. The percutaneous approach can be an alternative for patients at high surgical risk.